2011
DOI: 10.4141/cjas2011-044
|View full text |Cite
|
Sign up to set email alerts
|

Review:Trans-forming beef to provide healthier fatty acid profiles

Abstract: Dugan, M. E. R., Aldai, N., Aalhus, J. L., Rolland, D. C. and Kramer, J. K. G. 2011. Review: Trans- forming beef to provide healthier fatty acid profiles. Can. J. Anim. Sci. 91: 545–556.Trans fatty acids are found naturally in foods, particularly in those derived from ruminant animals, such as beef and dairy cattle. Over the past few decades, human consumption of trans fatty acids has increased, but this has been mainly from products containing partially hydrogenated vegetable oils. The correlation of trans fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 97 publications
2
49
0
Order By: Relevance
“…Kalscheur et al (1997) reported that low ruminal pH reduces rates of ruminal BH with a decrease of CLA and trans C18:1 percentages, suggesting an inhibition of the isomerase (Troegeler-Meynadier et al, 2006). Dugan et al (2011) reported that cattle that were fed grain with highly fermentable starch shifted in the BH pathways on the expense of VA VA. Increased the content of t10-18:1 and decreased the content of VA, consequently reduced ratio of t11-18:1 to t10-18:1 in PCD muscle by feeding wheat in the place of barley grain in the present study were likely attributed to the low ruminal pH as resulted from rapidly fermented wheat starch in the rumen our unpublished data).…”
Section: Substituting Wheat For Barleymentioning
confidence: 98%
See 1 more Smart Citation
“…Kalscheur et al (1997) reported that low ruminal pH reduces rates of ruminal BH with a decrease of CLA and trans C18:1 percentages, suggesting an inhibition of the isomerase (Troegeler-Meynadier et al, 2006). Dugan et al (2011) reported that cattle that were fed grain with highly fermentable starch shifted in the BH pathways on the expense of VA VA. Increased the content of t10-18:1 and decreased the content of VA, consequently reduced ratio of t11-18:1 to t10-18:1 in PCD muscle by feeding wheat in the place of barley grain in the present study were likely attributed to the low ruminal pH as resulted from rapidly fermented wheat starch in the rumen our unpublished data).…”
Section: Substituting Wheat For Barleymentioning
confidence: 98%
“…Dugan et al (2007) reported that the most prominent trans-18:1 isomers in feedlot back fat were 10t-18:1 and vaccenic acid (t11-18:1; VA). In addition, Dugan et al (2011) reported that cattle that were fed grain with highly fermentable starch shifted in the BH pathways towards producing t10-18:1 from VA. There is little information available on the effect of high wheat grain diet on fatty acid profile in beef.…”
Section: Introductionmentioning
confidence: 97%
“…The two major sources of t-18:1 isomers include industrially produced partial hydrogenated vegetable oils (iTFA) and naturally produced fats found in dairy and meat products from ruminant animals (Dugan, Aldai, Aalhus, Rolland, & Kramer, 2011). Ruminant TFA (rTFA) are produced by microbial enzymes through complex processes that involve isomerization and biohydrogenation of dietary PUFA in the rumen, and are absorbed and deposited in tissue lipids (Fig.…”
Section: Trans-octadecenoic Fatty Acids In Beefmentioning
confidence: 99%
“…When provided with an adequate forage-to-concentrate ratio, microbial populations favour t11-18:1 formation during 18:2n-6 and 18:3n-3 biohydrogenation (Lourenço, Ramos-Morales, & Wallace, 2010;Shingfield et al, 2010). However, when fed a high concentrate diet, rumen pH decreases, microbial populations are affected and biohydrogenation pathways shift whereby t10-18:1 becomes the predominant t-MUFA (Bessa, Portugal, Mendes, & Santos-Silva, 2005;Dugan et al, 2011;Leheska et al, 2008). Although the present bison did not indicate such an extreme shift, the t11-/t10-18:1 ratio did decrease in relation to increasing proportion of concentrate in the diet.…”
Section: Discussionmentioning
confidence: 99%